Transforming Growth Factors α and β Are Essential for Modeling Cholangiocarcinoma Desmoplasia and Progression in a Three-Dimensional Organotypic Culture Model - Manzanares, Miguel Á. (Am J Pathol, 2017)
To gain insight into the cellular and molecular interactions mediating the desmoplastic reaction and aggressive malignancy of mass-forming intrahepatic cholangiocarcinoma (ICC), we modeled ICC desmoplasia and progression in vitro. A unique three-dimensional (3D) organotypic culture model was established; within a dilute collagen–type I hydrogel, a novel clonal strain of rat cancer-associated myofibroblasts (TDF(SM)) was co-cultured with a pure rat cholangiocarcinoma cell strain (TDE(CC)) derived from the same ICC type as TDF(SM). This 3D organotypic culture model reproduced key features of desmoplastic reaction that closely mimicked those of the in situ tumor, as well as promoted cholangiocarcinoma cell growth and progression. Our results supported a resident liver mesenchymal cell origin of the TDF(SM) cells, which were not neoplastically transformed. Notably, 3D co-culturing of TDE(CC) cells with TDF(SM) cells provoked the formation of a dense fibrocollagenous stroma in vitro that was associated with significant increases in both proliferative TDF(SM) myofibroblastic cells and TDE(CC) cholangiocarcinoma cells accumulating within the gel matrix. This dramatic desmoplastic ICC-like phenotype, which was not observed in the TDE(CC) or TDF(SM) controls, was highly dependent on transforming growth factor (TGF)-β, but not promoted by TGF-α. However, TGF-α was determined to be a key factor for promoting cholangiocarcinoma cell anaplasia, hyperproliferation, and higher malignant grading in this 3D culture model of desmoplastic ICC.